Pendidikan Nasionalisme di Era Society 5.0.: Revitalisasi Peran Keluarga dan Masyarakat - Dartono Dartono; Holimin Holimin; Djoko Prihantoro (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
In the Era of Society 5.0., when the threat of the existence of the nation state becameincreasingly complex, Indonesian nationalism indicated a decline. The degradation of the role of the family and society has had an impact on the role of education which until now is seen as not quite effective. This literature study on nationalism aims to explain the condition of Indonesian nationalism, family and society as the dominant factor, as well as revitalizing the role of education stakeholders in the development of nationalism in Era 5.0. By using the descriptive-qualitative method the study concludes as follows; (1) the construction of Indonesian nationalism is built on a strong foundation of perception and belief in colonialism as an external threat (common enemy) to the existence of the nation-state which continues to dominate the journey of national life until the Era of Society 5.0, (2) the role of the unity of fate (chiksalgemeinschaft) tends to stagnant along with the widening of various gaps in national life. The role of education also decreases along with the degradation of the role of family and society, (3) re-empowerment of the role of family and community is very vital in order to build strong perceptions and beliefs of all elements of society in understanding the counter belief of ideology of Pancasila, the flood of foreign products, and others as a threat. enemy) along with the existence of the nation state. One thing that can be done is empowering the role of the Village (Kelurahan) to better ensure the socialization and internalization process, including optimizing the use of village funds to support its operational implementation.